Development of Positive Law in Indonesia - M. Hafiz Kurnia; Lukmanul Hakim (Yayasan Adra Karima Hubbi, 2024)
Background. In the development of positive law today, especially after the reform in Indonesia, there are several laws that the author considers to have developed, especially in terms of child protection law, in addition to those that have existed previously in the Criminal Code and Criminal Procedure Code both material and formal. Purpose. The blurring of the form of the rule of law caused by the lack of strengthening of the legal system implemented by the Indonesian state is one of the reasons for the many reasons for the need to establish an Indonesian Legal System. Method. The transition to democracy as one of the triggers for changes in the national legal system inevitably demands changes to the national legal system in a better direction in an effort to establish a national legal system that is in accordance with the ideals of the Indonesian state. Results. The development of national legal systems should remain long-term oriented in their application. Thoughts about the development of national law in the future have certainly been thought of from an early age in order to set the direction of national law development. Conclusion. The development of Indonesian national law which is currently strongly influenced by external elements as much as possible to maintain material legal sources from Indonesian laws. The development of national law that emphasizes the spirit of Indonesia and the taste of Indonesia can only be done by consensus from all elements of the nation.